Magnetic heterogeneity in electron doped La1-xCa xMnO3 manganites studied by means of electron spin resonance - V. Likodimos; Pissas, M. (Journal of Physics Condensed Matter, 2005)
Electron spin resonance (ESR) has been applied to investigate the magnetic heterogeneity in electron doped La1-xCaxMnO3 (0.80≤x≤0.95). A low field ferromagnetic resonance (FMR) mode is observed for lightly doped compounds (x = 0.90,0.95), signifying the formation of ferromagnetic (FM) spin clusters within the antiferromagnetic G-type AFM phase. The anomalous temperature variations of the resonance field, linewidth and FMR intensity, as well as the observation of thermal cycling effects below TC, emphasize the non-trivial dynamics of the FM phase, which is attributed to the temperature dependent size evolution of the underlying spin clusters towards canted AFM and FM domains. For heavier electron doping (x = 0.80,0.85), distinct AFM behaviour is evinced in the vicinity of TN in the monoclinic C-type AFM phase, characterized by the absence of critical relaxation. Additional weak FMR lines are observed for x = 0.80 and 0.85, whereas a narrow superparamagnetic-like signal is detected for x = 0.95. © 2005 IOP Publishing Ltd.